Respuesta :

For this case we have the following equation:

[tex]3 (b + 4) + 8 = -3[/tex]

If we apply distributive property to the terms within the parenthesis we have:

[tex]3b + 12 + 8 = -3[/tex]

We add similar terms to the left side of the equation:

[tex]3b + 20 = -3[/tex]

Subtracting 20 from both sides of the equation:

[tex]3b = -3-20\\3b = -23[/tex]

Dividing between 3 on both sides of the equation:

[tex]b = - \frac {23} {3}[/tex]

In mixed number we have:

[tex]b = -7 \frac {2} {3}[/tex]

Answer:

[tex]b = -7 \frac {2} {3}[/tex]